Membrane biogenesis, assembly and targeting (general methods, eukaryotes) - Fleischer, Sidney; Fleischer, Becca (Methods in enzymology, 1983)
FROM THE PREFACE: Volumes 96 to 98, Parts J, K, and L of the Biomembranes series, focus on methodology to study membrane biogenesis, assembly, targeting, and recycling. This field is one of the very exciting and active areas of research. Future volumes will deal with transport and other aspects of membrane function.